Lieutenant II Muradi and the Guerrilla Struggle Against the Dutch: War Tactics in Military Aggression II in Kerinci (1948-1949) - Alhuzaini, Muhammad; Sudarman, Sudarman; Aisyah, Siti (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
After the end of Japanese colonialism in Indonesia, the Dutch wanted to re-colonize Indonesia with the help of the Allies. Indonesia strongly opposed the Dutch plan, so there was great resistance from the Indonesian people and the Dutch began to carry out Military Aggression I and II in various regions, including Kerinci. In the Dutch Military Aggression in Kerinci,  lieutenan II Muradi became a very important figure because he led and organized the guerrilla war strategy against the Dutch. The main focus of this research is to look at the role of  lieutenant II Muradi and the war tactics used with his troops in the face of superior Dutch military strength. The method used in this paper is the historical method. The results show that  lieutenant II Muradi, who came from Koto Tuo Village, Kerinci Regency, completed his education at the SR CVO and the Vocational College in Bengkulu, then became a teacher in Bengkulu. During the Japanese occupation, he was appointed to the Gyugun, or Japanese auxiliary army, with the rank of Sergeant Major. In Dutch Military Aggression II, he led the war using guerrilla tactics, scorched earth tactics, and readiness detection against the Dutch. His contribution to the struggle in Kerinci is highly respected, as evidenced by the establishment of a monument to his struggle in Sungai Penuh City, Kerinci, and the naming of a protocol road in Kerinci Regency.